Influence of protein kinase C inhibitor in phagocytosis activity toward Candida sp (Faculty of Medicine Universitas Indonesia, 2001)
Protein kinase C isoenzyme family that expresses in all of cells plays a pivotal role in the signal transduction pathway of a variety of hormones, cytokines, neurotransmitter, and growth factors. The immunity against Candida sp is mainly mediated and performed by the T cells and macrophages. The objective of this experiment is to know the influence the protein kinase C inhibitor - bisindolylmaleimides in phagocytosis activity toward Candida sp. The culture of peritoneal macrophage derived from BALB/c mice are treated with bisindolylmaleimides as a protein kinase C inhibitor concentration varied from 5 ng/ml to 100 ng/ml for as long as 1 minute. Then the Candida sp added is observed after every 30 minute for as long as 120 minute. As the experimental design is used themethod of factorial and orthogonal polynomial. The data consisting the length of pseudopodia and the number of Candida sp which are phagocytosed are analyzed applying the Anova. One Way Anova to show the differences of each manipulation, the Two Way Anova to show the interaction of manipulations and the Student's t Test to show the differences with control. Statistical test show significant differences on the length of pseudopodia, and phagocytosed Candida sp, at different bisindolylmaleimides concentration (p<0.001) and different observed time (p<0.001). The data show a significant interaction between the bisindolylmaleimides concentration and observed time (p<0.001). The higher the bisindolylmaleimides concentration, the earlier the observed time, the much number the protein kinase C are going inactive and the shorter the length of pseudopodia or the lower the macrophages phagocytic activity toward Candida sp. The result of this experiment indicates that bisindolylmaleimides can inhibit the macrophage mobility and phagocytic activity toward Candida sp. Further experiment in protein kinase C, especially in macrophage, is suggested. (Med J Indones 2001; 10: 150-7)